Need Analysis for Differentiated Learning Media to Facilitate Students with Different Learning Styles - Ramadhaniyah, Qonita; Asmiyah, Siti; Amaliya, Fitria (ICONELT, 2024)
Each student is unique in their learning style. Hence, for teaching and learning to be effective and efficient, the methods used should be adjusted to meet the student's learning preferences and needs in order to be understood effectively. This research aims to analyze students' learning styles and to identify the learning media students prefer to facilitate their English learning. Using a qualitative approach, the data on learning style was collected through a learning style test involving students from grade 7. The students also responded to questionnaires on their preference for learning media. The teachers' interviews were also conducted to further explore the learning media used. The data highlight that students in the majority are of kinesthetic and visual styles; 39.4% of each style, while 21.2% are auditory. For the learning media, the kinesthetic students tend to like interactive media and projects; visual students prefer books, pictures, videos, and slides; auditory students prefer direct explanation from the teacher, music, and audio. The results of interviews with teachers show that teachers apply learning media in the form of textbooks and direct explanations more often. This is because the school has not yet implemented differentiated learning. Despite this, teachers also occasionally apply interactive learning media during learning. Teachers stated that there is a difference in the effectiveness of traditional learning and interactive media. This finding implies that in ELT, teachers who teach this group of students can use videos and interactive media to accommodate the three learning styles of students.